O conhecimento sobre os números racionais nas turmas de 9º ano do ensino fundamental e de 3º ano do ensino médio da Escola Estadual de Ensino Fundamental e Médio Professor Aluízio Lopes Martins. se estão equiparados de fato no que se pretende saber nas referidas séries sobre tais números. - VIEIRA, Gesiney de Melo (Universidade Federal do Oeste do Pará, 2024)
This article seeks to show how knowledge, knowledge of fact about rational numbers in the 9th grade classes and in the 3rd grade classes of the State School of Elementary and Middle School Professor Aluízio Lopes Martins in Santarém of Pará. We are living in a context in which society is inserted in an environment where it is possible to have access to countless information at an extraordinary speed. If it is then verified, if in fact a certain sample of students of the school under study are in their referred series with the basic knowledge on Rational Numbers. In this research work, the historical aspects will be put into relevance and the methodologies and didactics related to numbers will be questioned, considering the network of meanings and meanings that are interrelated in particular the proper understanding and usefulness of rational numbers. For this, a questionnaire was organized with several situations involving rational numbers that can be analyzed through this one with respect to the use of rational ones, nevertheless there will be a convergence between the ideas and the meanings assigned to these rational numbers, in order to make possible the problematization and the reflection on the use of them. In general, all the strategies used in the production of this work were to evaluate the adequacy and quality of the teaching of rational numbers in Elementary and Middle School to highlight some methodological choices and some didactic resources for the teaching of contents where rational ones are made gifts.